Somewhat Opinionated A dance journal - Barnes, Clive 1927-2008 (Dance Books Ltd., Alton,Hampshire (UK), 2005)
Kennedy Center, Washington, DC, 22 June. Metropolitan Opera House, New York, 5 July. Kennedy Center, Washington, DC, 9 July. Joyce Theater, New York, 11 July. Rose Theatre, Lincoln Center, New York, 13 July. Metropolitan Opera House, New York, 18 July. New York State Theatre, New York, 21 July. New York State Theatre, New York, 23 July. New York State Theatre, New York, 25 July. New York State Theatre, New York, 28 July. Joyce Theatre, New York, 8 August. Copenhagen, 17 August. Sadler's Wells Theatre, London, 26 August. Sadler's Wells Theatre, London, 6 September. Victoria Palace Theatre, London, 13 September. Sadler's Wells Theatre, London, 15 September. Prince Edward Theatre, London, 23 September. City Center, New York 27 September-2 October. PALABRAS CLAVE: The Capezio Dance Award, Suzanne Farrel, Don Quixote, American Ballet Theatre, Kirov Ballet, Pilobolus, The Merce Cunningham Dance Company, Lincoln Center Festival, Diaghilev Russian Ballet, Wayne McGregor's Random Dance, Yuri Grigorovich, Alexander Ratmansky, Pierre Lacotte, Hubbard Street Dance Chicago, Bournonville Festival, Matthew Bourne, Billy Elliot, Stephen Daldry, Fall for Dance Festival.